Analysis of Attributes That Become Consumer Preferences on Bag Products - Putri, Shafira Mardiani Rizkia (Universitas Ciputra Surabaya, 2022)
Efve atelier is a local brand from Surabaya which bag is its main product. Several late editionsissued a decrease in turnover. One of the main possible reason is the lack of variety of model produced.There are many important attributes that influence consumers when making a purchase. Therefore, thisstudy was conducted to determine the combination of attributes that become consumer preferences for bagproducts. This research used descriptive quantitative analysis using conjoint analysis. The three attributesobtained from preliminary survey and previous researches are design, color, and material. The threeattributes have two levels of each attribute then the stimulus is designed using SPSS software and obtained8 stimuli. The population of this study are Efve’s consumers and potentiol new consumers with a total of 70people. The research sample used was 60 people with purposive sampling technique. Based on the results, itis known that the combination of consumer’s prefered attributes for bag products are a combination ofwarm cool colors, frame bag designs and fabrics. It can also be seen that the attribute that is considered themost important is the color attribute followed by the design and material.